2019
DOI: 10.1177/1455072519845970
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and illicit drug consumption and the association with risky sexual behaviour among Swedish youths visiting youth health clinics

Abstract: Aims: High alcohol consumption and use of illicit drugs among young people is of great concern and there is a need to identify arenas where this group can be reached by preventive measures. The aim of the present study was to study prevalence of risky alcohol consumption, illicit drug use, and risky sexual behaviour (RSB) among young people visiting youth health clinics in Stockholm county. Another aim was to explore the association between risky alcohol consumption, illicit drug use and RSB. Methods: During a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
(64 reference statements)
1
17
0
1
Order By: Relevance
“…Concerning the variables, despite the item of alcohol consumption being designed primarily for clinical purposes and perhaps too rough, it still yielded similar results as studies using AUDIT-C in the youth clinic setting ( 10 ). A strength of our study is the collection and reporting of data on non-binary and transgendered people, often excluded in research explained by small numbers, but sometimes also on ignorance when collecting and reporting data ( 40 ).…”
Section: Discussionmentioning
confidence: 65%
“…Concerning the variables, despite the item of alcohol consumption being designed primarily for clinical purposes and perhaps too rough, it still yielded similar results as studies using AUDIT-C in the youth clinic setting ( 10 ). A strength of our study is the collection and reporting of data on non-binary and transgendered people, often excluded in research explained by small numbers, but sometimes also on ignorance when collecting and reporting data ( 40 ).…”
Section: Discussionmentioning
confidence: 65%
“…In Sweden, alcoholic beverages can be legally purchased from the age of 20, and in bars and restaurants, alcoholic beverages may be ordered from the age of 18. Nevertheless, in a national survey of adolescents aged 15-16 years, 40% reported use of alcohol during the past year [ 6 ], and Strandberg and coworkers [ 7 ] found that, among adolescents and young adults aged 15–27 years visiting youth health clinics in Stockholm, Sweden, 62% reported a “risky alcohol use.” In a longitudinal study, Danielsson et al found that one episode or more of heavy drinking, i.e., binge drinking, predicted continued irregular heavy drinking two years later in boys, and the same trend was shown for girls [ 8 ]. Binge drinking is an important aspect of risky alcohol use, strongly linked to fights and withdrawal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in sexual risk behaviours will be measured by multiple choice questions on sexual behaviour under the influence of alcohol and/or other substances and unprotected sex, previously used in a survey among Swedish visitors at youth health clinics in Stockholm County. 86 Changes in perceived peer pressure will be measured by two items retrieved and adapted from the peer pressure inventory. 87 Perfectionism will be measured by two subscales of the Frost Multidimensional Perfectionism Scale.…”
Section: Methodsmentioning
confidence: 99%